2020
DOI: 10.3389/fphys.2019.01612
|View full text |Cite
|
Sign up to set email alerts
|

Familial Dilated Cardiomyopathy Associated With a Novel Combination of Compound Heterozygous TNNC1 Variants

Abstract: Familial dilated cardiomyopathy (DCM), clinically characterized by enlargement and dysfunction of one or both ventricles of the heart, can be caused by variants in sarcomeric genes including TNNC1 (encoding cardiac troponin C, cTnC). Here, we report the case of two siblings with severe, early onset DCM who were found to have compound heterozygous variants in TNNC1: p.Asp145Glu (D145E) and p.Asp132Asn (D132N), which were inherited from the parents. We began our investigation with CRISPR/Cas9 knockout of TNNC1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Steady-state isometric force data were analyzed and fit using a two-or three-parameter sigmoidal Hill equation as previously described. 19,36,37 Rate of Tension Redevelopment (k TR ): Briefly, after force levels reached a steady state at different Ca 2+ activation levels, measurements of the rate of tension redevelopment were obtained by shortening a CMP by 20% of its original length (L 0 ), followed by a rapid 25% restretch, and shortened back to L 0 . 36−38 The CMP lengths were controlled using a high-speed servomotor model 322C from Aurora Scientific.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Steady-state isometric force data were analyzed and fit using a two-or three-parameter sigmoidal Hill equation as previously described. 19,36,37 Rate of Tension Redevelopment (k TR ): Briefly, after force levels reached a steady state at different Ca 2+ activation levels, measurements of the rate of tension redevelopment were obtained by shortening a CMP by 20% of its original length (L 0 ), followed by a rapid 25% restretch, and shortened back to L 0 . 36−38 The CMP lengths were controlled using a high-speed servomotor model 322C from Aurora Scientific.…”
Section: ■ Methodsmentioning
confidence: 99%
“…All experiments were performed at room temperature (21 °C). Steady-state isometric force data were analyzed and fit using a two- or three-parameter sigmoidal Hill equation as previously described. ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The double compound heterozygous DCM variant (E59D/D75Y) has also been shown to decrease myofilament Ca 2+ sensitivity and reduce strong actin–myosin binding [ 135 , 136 ]. A recent study by Landim-Vieira et al, 2019 on the missense compound heterozygous DCM-causing variants (D132N and D145E) demonstrated no significant changes in contractile parameters, indicating to the potential involvement of other pathological mechanisms beyond myofilament dysfunction [ 137 ].…”
Section: Cardiomyopathy Causative Mutations In Sarcomeric Proteinsmentioning
confidence: 99%
“…The emphasis should be on accurate quantification of defective phenotypes as they arise in the developing embryo and study of genes whose human orthologs are implicated in congenital disease. X. tropicalis knock-outs have already been used as part of large, multi-species studies that confirm disease causality for candidate genes identified through patient genome sequencing [13,88,89]. The real challenge is to move beyond functional-nulls and to replicate the actual missense mutations found in patients, which are likely to encode far subtler hypomorphic changes to protein activity.…”
Section: Laevis and X Tropicalis Are Suited To Different Types Of Gene Editing Projects (At The Moment)mentioning
confidence: 99%